Legal Reformulation of the Transfer of Rights To Guaranteed Objects Through Foreseen Collateral - Yuniar, Lisa Mega; Dewantara, Reka; Jauharoh, Arini (Faculty of Law, University of Jember, Indonesia, 2025)
Foreclosed Assets is one of the mechanisms used by banks in settling non-performing loans without having to go through lengthy and complicated auction procedures. Although the Foreclosed Assets mechanism has been regulated under Article 12A of Law No. 4 of 2023 on Development and Strengthening of the Financial Sector, in practice—particularly in the context of bankruptcy—there remains legal uncertainty. This is due to inconsistent regulations between the Mortgage Law, the Banking Law, and Supreme Court Circular No. 3 of 2023. This research aims to analyze the Foreclosed Assets mechanism juridically within the context of bankruptcy and to formulate a reformulation of legal arrangements concerning the transfer of rights over collateral objects through the Foreclosed Assets mechanism to ensure legal certainty. This study employs a normative juridical method using statute and conceptual approaches. The results of this study show that the implementation of Foreclosed Assets, both through auction and outside auction, has different legal consequences. Foreclosed Assets conducted through auction has a sufficiently strong legal basis, while Foreclosed Assets conducted outside auction—which generally uses Sale and Purchase Agreement and Power of Attorney to Sell—still presents legal uncertainty. This is due to the absence of technical regulations specifically governing the procedures and forms of documents in the implementation of Foreclosed Assets outside auction. Furthermore, the use of PPJB as the legal basis for the transfer of rights in Foreclosed Assets practice has the potential to conflict with the pactum commissorium principle as regulated in the Mortgage Law. This reformulation is essential to clarify the legal position of banks over acquired collateral as well as to uniformly regulate valid legal document formats in the Foreclosed Assets mechanism, thereby providing legal certainty for banks, debtors, notaries, receivers, and other related parties.